Polymeric Micro/Nanomotors and Their Biomedical Applications. Issue 18 (10th June 2021) - Liang, Ziying; Tu, Yingfeng; Peng, Fei
Abstract: Since their naissance in the 2000s, various micro or nanomotors with powerful functions have been proposed. Among them, polymer‐based micro or nanomotors stand out for the easy processing and facile functionalization, holding immense potential for bioapplications. In this review, fabrication of polymer‐based micro or nanomotors and their applications in biomedical areas are covered. Classic manufacturing approaches as well as cutting‐edge techniques are discussed with representative works highlighted. Current challenges and future prospects are presented in the hope of pointing new research directions to facilitate practical translations of micro/nanomotors. Abstract : With superb moving and processing features, polymeric motors promise to revolutionize bioapplications. In this review, classic and the most recent fabrication approaches of polymer‐based micro/nanomotors, cutting‐edge biomedical applications, ranging from drug delivery, cell manipulation, and biosensing are covered. In an attempt to accelerate practical translations, challenges and prospects of polymeric micro/nanomotors are analyzed and discussed in depth.